Allocating Logging Rights in Peruvian Amazonia-Does It Matter to Be Local? - Salo M; Helle S; Toivonen T (PUBLIC LIBRARY SCIENCE, 2022)
Conclusions/Significance: The allocation process left a considerable number of forest areas under the management of small and local actors, and if Peru is to reach its goal of zero deforestation rate by safeguarding 75 per cent of its forests by 2020, the small and the local actors need to be integrated to the forest regime as important constituents of its legitimacy.